Kepemimpinan Etis pada Penerapan Strategi CSR dalam Perspektif Asta Brata - Anindita, Ria; Hamidah, Hamidah (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
The leader's approach to the CSR program has positive results on achieving loyalty and customer satisfaction which can affect CSR performance. Weak public pressure on CSR reporting makes leaders understand the importance of CSR disclosure in company policy. The search for ethical leadership values can follow the teachings of Asta Brata's leadership values. The value of Asta Brata in describing the reality of CSR will be easier to digest and learn by using metaphors, especially for those who do not have direct experience. Asta Brata values include Mahambeg Mring Samudro, Mahambeg Mring Maruto, Mahambeg Mring Bhumi, Mahambeg Mring Angkasa, Mahambeg Mring Condro, Mahambeg Mring Dahana, Mahambeg Mring Suryo, and Mahambeg Mring Kartika. This value is the value that ethical leaders must have in influencing employees towards the goals of a shared CSR strategy. Value Asta Brata can answer the phenomenon of CSR programs but only symbolically and does not have ethical elements and concern for social and community issues. Keywords: Ethical Leadership; CSR; Asta Brata; Metaphor.